Electromechanical energy conversion through active learning - Cardoso, José Roberto; Salles, Maurício Barbosa de Camargo; Costa, M. C. (Mauricio Caldora) (IOP ebooks. 2020 collection., 2020)
This book introduces electromechanical energy conversion through active learning. Covering linear and non-linear magnetic circuits, transformers, electromechanical energy and forces, and excited electromechanical systems, along with detailed examination of various machines involved, the book contains numerous 'hands-on' challenges that encourage a creative and determined approach to problem-solving, making it an ideal text for undergraduate courses.